Plant-Derived Phenolic Compounds From Molecular Mechanisms to Clinical Application - Castellani, Stefano; Conese, Massimo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Plant-derived phenolic compounds whose most important classes are flavonoids (i.e., catechin, epicatechin) quinones, stilbenes (i.e., resveratrol) and essential oils (i.e., thymol, carvacrol), widely found in fruits, seeds, flowers, and leaves, are considered as beneficial molecules for prevention and treatment of several diseases, since it has been shown that they have antioxidant, anticarcinogenic, cardioprotective, neuroprotective, and anti-inflammatory properties. The Special Issue contains contributions concerning different aspects of the use of phenolic plant-derived molecules for prevention and therapy of several diseases, in order to understand the mechanisms involved in their protective role, their bioavailability and their metabolism in human tissue. Moreover, the use of different strategies for extraction, synthesis, and delivery of these compounds, has been covered.